A regional bio-economic model of nitrogen use in cropping - Mérel, P.; Yi, F.; Lee, Juhwan; Six, J. (2014)
We develop a programming model of crop production to predict the effects of environmental policies on agriculture and the environment. The model is calibrated against acreages, yields, and exogenous supply elasticities following positive mathematical programming. In addition, crop production functions are calibrated to yield elasticities with respect to nitrogen and irrigation obtained from a biogeochemical model. We study the effects of a nitrogen tax in Yolo County, California, intended to mitigate nitrogen pollution from field crops. The behavioral and environmental responses to the tax are largely due to intensive margin adjustments. Sizable reductions in nitrate leaching are achieved at a low social cost. © 2013 The Author (2013). Published by Oxford University Press on behalf of the Agricultural and Applied Economics Association. All rights reserved.